2022
DOI: 10.3390/land11091599
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Spatial Plans Adopted at the Local Level in the Spatial Planning Systems of Central and Eastern European Countries

Abstract: The article deals with the issue of spatial plans at the local level. The aims of this paper are (1) extracting the characteristics of local spatial plans that can be compared more broadly (2) identifying, on this basis, the role of spatial plans at the local level in the countries of Central and Eastern Europe (CEE). In achieving these aims, the authors have critically examined spatial plans and their performance, as well as the planning systems they belong to. Hence, they have investigated the types of local… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 51 publications
0
7
0
Order By: Relevance
“…Other studies that have been carried out show that there is a significant problem with the implementation of spatial plans at the local level in a large number of countries [2]. The studies show that these plans are not coordinated with other spatial planning instruments, and even less so, with strategic planning instruments.…”
Section: Conclusion and Summarymentioning
confidence: 91%
See 1 more Smart Citation
“…Other studies that have been carried out show that there is a significant problem with the implementation of spatial plans at the local level in a large number of countries [2]. The studies show that these plans are not coordinated with other spatial planning instruments, and even less so, with strategic planning instruments.…”
Section: Conclusion and Summarymentioning
confidence: 91%
“…This article is a continuation of previous research on the countries indicated. In particular, common features and differences related to spatial plans at the local level have been analyzed [2]. Other research shows that there are serious systemic problems in the individual countries of the region (Ukraine and Poland were analyzed in detail) [3].…”
Section: Socio-geographical Researchmentioning
confidence: 99%
“…Similarly, other central and eastern European countries restructured their spatial planning and management system. For most countries, this restructuration has been steered and eased by the process of adhesion to the European Union [41][42][43].…”
Section: Municipal Master Plan Operationalmentioning
confidence: 99%
“…), by the real estate characteristics, which influence the profitability of the investment (Chmielewska, Ciski and Renigier-Biłozor, 2022), as well as by local public administration decisions in the field of urbanism, so as to allow the development of different types of projects (Stan, 2021a). Authorities in the field of planning must consider economic, socio-cultural structures, administrative forms and priorities (Stan and Vintilă, 2021a) as plans delineate areas, define development parameters and impose restrictions on development and in relation to the real estate market (Nowak et al, 2022).…”
Section: Literature Reviewmentioning
confidence: 99%